The celestial track of the green field two chinese translations of: The wonderful wizard of Oz - Han, Luyao Luna (My University, 2014)
This research report is an attempt to broaden somewhat the body of knowledge on the topic of the translation of children’s literature, in this case from English to Chinese. Using concepts from relevance theory and reception theory, this research report examines two Chinese translations of a famous American children’s story, The Wonderful Wizard of Oz. By conducting a comparative analysis of two Chinese translations, one produced in the early 1950s and the other produced in 2012, I examine how different translation approaches were used to cater to their respective target audiences in the vastly different cultural context of the insular and conservative China in the 1950s and globalised China of the early 21st century. I use relevance theory and reception theory to account for the shifts in the two translations showing how the respective Chinese translators dealt with the cultural mediation of an American children’s story to their young Chinese audiences in very different moments in Chinese history.